2009
DOI: 10.1002/humu.20874
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutations in the ribosomal protein L5 (RPL5) and ribosomal protein L11 (RPL11) genes in Czech patients with Diamond-Blackfan anemia

Abstract: Diamond-Blackfan anemia (DBA) is a congenital red blood cell aplasia that is usually diagnosed during early infancy. Apart from defects in red blood cell maturation, the disorder is also associated with various physical anomalies in 40% of patients. Mutations in the ribosomal protein (RP) S19 are found in 25% of patients, while mutations in other proteins of the small ribosomal subunit-RPS17 and RPS24-have been found in a fraction of patients. Recently, mutations in RPL5, RPL11, and RPL35a of the large ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 23 publications
6
82
0
6
Order By: Relevance
“…This feedback regulation may also act as an intrinsic mechanism or surveillance for controlling cell transformation and tumorigenesis because defects of this pathway could lead to deregulated c-Myc activity and tumorigenesis. Recently, it was shown that haploinsufficiency of L11 and other ribosomal proteins, due to loss of function gene mutations or deletions, occurs in patients with Diamond-Blackfan anemia (27,28), an inherited disorder with bone marrow failure and increased incidence of cancer formation (29). It will be interesting to test if c-Myc activity is enhanced and contributes to cancer susceptibility in this disorder in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…This feedback regulation may also act as an intrinsic mechanism or surveillance for controlling cell transformation and tumorigenesis because defects of this pathway could lead to deregulated c-Myc activity and tumorigenesis. Recently, it was shown that haploinsufficiency of L11 and other ribosomal proteins, due to loss of function gene mutations or deletions, occurs in patients with Diamond-Blackfan anemia (27,28), an inherited disorder with bone marrow failure and increased incidence of cancer formation (29). It will be interesting to test if c-Myc activity is enhanced and contributes to cancer susceptibility in this disorder in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] More recently, Gazda et al identified mutations in RPL5 and RPL11 in an additional 11.4% of patients and noted that mutations in RPL5 were associated with a higher frequency of physical abnormalities, including cleft lip and/or palate, whereas mutations in RPL11 had more isolated thumb abnormalities compared with patients with mutations in RPS19. 20 Subsequent work by the Czech DBA registry revealed that, in the 10 patients with either a RPL5 or RPL11 mutation, there was a thumb abnormality, whereas none 21 This may indicate that mutations in different ribosomal genes lead to distinct clinical phenotypes. A large-scale screen of RP genes in the DBA population has also revealed candidate mutations in RPS7, RPL36, RPS15, and RPS27A.…”
Section: Diamond-blackfan Anemiamentioning
confidence: 99%
“…by guest www.bloodjournal.org From of the 7 patients with RPS19 mutations in the registry exhibited such an anomaly. 21 This may indicate that mutations in different ribosomal genes lead to distinct clinical phenotypes. A large-scale screen of RP genes in the DBA population has also revealed candidate mutations in RPS7, RPL36, RPS15, and RPS27A.…”
Section: Diamond-blackfan Anemiamentioning
confidence: 99%
“…These genes encode for RP of either the small or the large ribosomal subunit. [3][4][5][6][7] The identification of the role of another RP gene, RPS14, in the pathogenesis of an acquired myelodysplastic disease, the 5q-syndrome, has recently attracted great interest, since it extends the spectrum of ribosomal diseases. 8 A clear genotype-phenotype correlation is not apparent in patients with RPS19 mutations, and identical mutations have been found in patients with a wide range of clinical presentations, even within the same family.…”
Section: Introductionmentioning
confidence: 99%